Gross efficiency during high intensity exercise - Noordhof, D. A.; Foster, C.; de Koning, J. J. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Gross efficiency (GE), the ratio between mechanical power output and metabolic power input, can be determined reliably during steadystate exercise performed below the ventilatory threshold. However, athletic performances are mostly completed at an intensity above the ventilatory threshold, what excites our interest in GE during high intensity exercise. To gain insight in GE during and after high intensity exercise de Koning et al. (2013) proposed a new methodology. Using this methodology, GE is determined during submaximal exercise performed before and after high intensity exercise, which allows GE to be estimated, using back-extrapolation, at the end of high intensity exercise (GEend). In a follow-up study this methodology was applied to cycling time trials. It was shown that GE decreased significantly during time trials with a length varying between 500 and 40,000 m and that the decrement in GE differed between distances (F = 5.49, P = 0.001). GE at the end of time trial exercise differed significantly between the 1,000 and 15,000 m and 1,000 and 40,000 m (P < 0.05; 19.8 ± 1.4 vs. 21.2 ± 1.0%; 19.8 ± 1.4 vs. 21.4 ± 1.4%). Thus, although GE declined during all time trials, the magnitude of the decrement was smaller for the longer trials (15,000 and 40,000 m). It is assumed that a decrement in efficiency will be even more pronounced during technically more demanding sports, like speed skating. As it is more difficult to determine power output during speed skating and thus to obtain GE, insight in GE during skating was addressed by studying changes in push-off effectiveness. Push-off effectiveness deteriorated significantly in elite athletes during World Cup races, with a greater decline in push-off effectiveness during the 1,500 m (P < 0.05). In addition, for the 5,000 m the change in effectiveness was significantly associated with the change in skating velocity (â = -0.069, [-0.11, - 0.030]; Noordhof et al., 2014). Although the cause and effect relationship has not been investigated, it seems most likely from a biomechanical view that the deterioration in effectiveness (i.e. larger push-off angle) will result in a decrement in skating velocity. In conclusion, GE and push-off effectiveness deteriorate during high intensity exercise. Pacing strategy influences the magnitude of the decline, and, at least in skating, the decline is associated with a performance decrement.